A 52-week follow-up, multi-center, randomized, double-blinded comparison of efficacy and safety of two hyaluronic acid fillers for the treatment of moderate-to-severe nasolabial folds in Chinese population - Hui Shao; Lu Wang; Jieying Tang; Lujia Chen; Shihong Zhang; Qiang Chen; Chuan Wang; Jianmin Yang; Weiwei Li; Hongyi Zhao (Taylor & Francis Group, 2024)
Introduction To investigate the efficacy and safety of Cutegel® MAX (Cutegel) in the correction of moderate-to-severe nasolabial folds (NLFS) compared to Restylane® (Restylane, control).Methods This study was a 52-week, multicenter, randomized, double-blinded, active-controlled clinical trial. Qualified participants with moderate-to-severe NLFs were randomly assigned in a 1:1 ratio to receive Cutegel or Restylane. For the primary efficacy endpoint, the response rate was defined as the percentage of subjects exhibiting an improvement of at least one-point based on blinded evaluation of Wrinkle Severity Rating Scale (WSRS) at 24 weeks after injection. Other secondary efficacy endpoints and treatment-emergent adverse events (TEAEs) were assessed.Results Of 340 subjects randomized, 317 completed the week 52 visit. In the per protocol set (PPS), the blinded evaluator-assessed response rates at week 24 were 81.17% for Cutegel versus 77.56% for Restylane (p =  0.327). The between-group treatment differences in response rates were 3.60% [95% confidence interval (CI) = (−5.39%, 12.60%)], which demonstrated the noninferiority of Cutegel. Other secondary efficacy endpoints supported this. No significant differences were observed in the occurrence of adverse events between the two groups.Conclusion Similar to Restylane, Cutegel was effective and well tolerated in correcting moderate-to-severe NLFs among the Chinese population.